The Effect of Human Resource Quality and Work Ethic on Employee Performance with Organizational Commitment as an Intervening Variable at Bank Indonesia Representative Office in North Sumatra Province - Leo Fauzi Hasibuan; Kiki Farida Farine (International Journal of Management, Economic and Accounting, 2024)
This study was conducted to determine the influence of human resource quality and work ethic on employee performance with organizational commitment as an intervening variable at the Bank Indonesia Representative Office in North Sumatra Province. Achieving effective and efficient corporate goals requires the continuous implementation of internal human resource management. The efficacy and efficiency of a company are highly dependent on the advantages and disadvantages of resource development. This means that the company's human resources must be developed and nurtured in order to be able to improve their work capabilities, which will ultimately have an impact on improving performance. The results of this study are as follows: Work Ethic has a positive and insignificant effect on Employee Performance with the original sample of 0.079 and p values of 0.322. Work Ethic had a positive and significant effect on Organizational Commitment with the original sample of 0.665 and p values of 0.000. Organizational Commitment has a positive and significant effect on Employee Performance with an original sample value of 0.831 and p values of 0.000. The quality of human resources had a positive and insignificant effect on Employee Performance with the original sample value of 0.020 and p values of 0.428. The quality of human resources has a positive and significant effect on Organizational Commitment with the original sample value of 0.263 and p values of 0.006. Work Ethic has a positive and significant effect on Employee Performance through Organizational Commitment indirectly with the original sample value of 0.552 and p values of 0.000. The quality of human resources has a positive and significant effect on Employee Performance through Organizational Commitment indirectly with the original sample of 0.218 and p values of 0.009.